THE REGENERATION OF THE MIDDLE-EAR MUCOSA OF THE RAT - (:unkn) unknown (KARGER, 1995)
The purpose of the study was to investigate the regeneration of middle ear mucosa following surgical removal and to observe the effects of Silastic sheetings on regeneration. Two weeks after the operation the middle ear cavity was covered by moderately differentiated epithelium in the animals which had only the mucosa removed. In animals with inserted Silastic sheeting, infection slowed down the regeneration process. During the 2 months of postoperative observation, the surface of the cavity appeared to be rough, and there was intensive fibrin deposition over the mucosa. It is concluded that normal middle ear mucosa regenerates rapidly after surgical removal. On the other hand and in contrast to the purpose of its usage, Silastic sheeting slows down the process and causes fibrosis.
Keywords: MIDDLE EAR MUCOSA; REGENERATION; SILASTIC SHEETINGS